P-365 Lesbian Shared IVF (ROPA) and IVF with donated semen – changing the recipient has no impact on reproductive outcomes. (30th June 2022) - Brandão, P; Ceschin, N; Cruz, F; Sousa-Santos, R; Reis-Soares, S; Bellver, J
Abstract: Study question: Are ROPA outcomes different from IVF with donated semen? – does the absence of genetic links between embryo and uterus impact reproductive outcomes? Summary answer: The ROPA method has similar reproductive success rates to conventional IVF with donated semen. What is known already: ROPA (reception of oocytes from partner), also known as lesbian shared IVF, is an assisted reproduction technique for female couples in which one woman provides the oocytes and the other receives the embryos, allowing both women to share biological motherhood. This technique may also be a way to assess the reproductive impact of the absence of a genetic link between the pregnant woman and the embryo. Broadly, it is an oocyte donation treatment, with the particularity that the patient's partner is the donor. In practice, this means that the donor may not be as young, healthy and fertile as usual. Study design, size, duration: Retrospective multicentric cohort study performed from January 2011 to December 2020 in 18 fertility clinics in Spain. A total of 99 ROPA (73 couples) and 2929 IVF cycles (2334 couples) were included. Participants/materials, setting, methods: ROPA and IVF cycles with donated semen of women younger than 38 years old and no know female fertility disorder were included. Clinical outcomes were compared between both groups, including positive pregnancy test, clinical pregnancy, miscarriage, ectopic pregnancy, preterm birth and live birth rates and weeks of gestation and newborn weight at birth. Main results and the role of chance: No differences were found between groups in clinical outcomes, including positive pregnancy test, clinical pregnancy, miscarriage, ectopic pregnancy and live birth rates, neither with fresh nor frozen embryo transfers. In addition, there were no differences in gestational age at birth, preterm birth rate or newborn weight. The total clinical pregnancy rates per embryo transfer were 57% and 50.2% (p = 0.15) and the live birth rates were 46.1% and 40.9% (p = 0.14) for the ROPA and IVF groups, respectively. When adjusted to age and BMI of donors and recipients, there were also no differences in live birth rates between both groups. The cumulative live birth rate per ROPA cycle was 73.7% and the cumulative live birth rate per couple was 78.3%. Limitations, reasons for caution: The retrospective nature of the study, the small sample size of the ROPA group, differences in age between both groups, the possibility of unknown other previous reproductive treatments, and the no analysis of obstetric and other neonatal complications and outcomes. Wider implications of the findings: Clinical outcomes of ROPA and single way IVF were similar, both after fresh and frozen embryo transfers. These findings suggest no impact of the absence of genetic ties between the embryo and the uterus on reproductive treatments' outcomes. Data regarding the outcomes of the ROPA method are reassuring. Trial registration number: 2011-VLC-093-PB